Effects of daily telephone-based re-education before taking medicine on Helicobacter pylori eradication: A prospective single-center study from China - Wang, Chun-Hua (World J Gastroenterol, 2015)
AIM: To investigate the effects of daily telephone-based re-education (TRE) before taking medicine for the eradication of Helicobacter pylori (H. pylori) on the compliance and the eradication rate in a Chinese patient population. METHODS: A prospective, physician-blinded, randomized, controlled clinical study was conducted. The patients were randomly assigned to receive TRE every day before taking medicine (TRE group) or no TRE (control group). The patients in the TRE group received regular instructions before taking medicine for the eradication of H. pylori during the entire course of treatment through telephone calls. The patients in the control group received detailed instructions at the time of seeing a doctor for the guidance. The primary outcome was the H. pylori eradication rate after treatment. The secondary outcomes included the clinical remissions after treatment, adverse events, compliance, and patients’ satisfaction. RESULTS: A total of 140 patients were randomized, 70 to the TRE group and 70 to the control group. As the primary outcome, the H. pylori eradication rates in the TRE and control groups were 62.7% and 71.2% in per protocol analysis (P = 0.230), and 52.9% and 52.9% in intention-to-treat analysis (P = 0.567), respectively. As the secondary outcomes, there were no significant differences in the patients’ satisfaction between the two groups (good, 79.7% vs 76.9%; fair, 13.6% vs 19.2%; poor, 6.7% vs 3.9%, for the TRE group and control group, respectively; P > 0.05 for all); the rates of adverse effects were 15.2% and 63.5% in the TRE and control groups, respectively (P < 0.001); the compliance rates in the TRE and control groups were 85.7% and 74.3%, respectively (P = 0.069). CONCLUSION: Daily TRE before taking medicine had no significant impact on the patients’ compliance, satisfaction, or H. pylori eradication, but reduced the rate of adverse events.